(untitled) (Raparin Journal of Humanities (RJH), 2024)
Al-Hazbany played a significant role in building and managing authority during the Middle Ages, establishing a Kurdish emirate within the Islamic state. Their influence extended beyond their homeland, as they journeyed thousands of kilometers towards Egypt and the Levant, actively participating in state affairs. Notably, the tribe made substantial contributions to scientific development, particularly during the eras of the Bahri Mamluks and Circassian kingdoms. The research comprises an introduction and two sections. The introduction sheds light on the origins of the Al-Hazbany tribe, their geographical presence, and their early political engagements, Especially in the Kurdistan regions, because they started their first political and military uprising in Kurdistan. The first section explores the multifaceted role of the tribe in the Bahri Mamluks kingdoms, covering administrative, scientific, religious, and literary aspects, Because with the disappearance of Ayyubid rule, the Hazbanis continued to provide scientific and administrative services. In the second section, the focus shifts to the Circassian kingdoms, providing insights into the administrative and scientific roles of the Hazbanys and their significant contributions to reconstruction. We note that during this period the Kurdish Hazbanis paid attention to the aspect of prayer، for example, the construction of mosques, scientific sites and even places known by their names, but it is not known why they were used.